Synthesis and characterization of poly(3‐thiophene acetic acid) upon binding by cationic groups. Issue 6 (21st December 2021) - Linh, Nguyen Ngoc; Thi, Tran Minh; Linh, Duong Khanh; Huong, Vu Thi; Hung, Ha Manh; Oanh, Doan Thi Yen; Trung, Vu Quoc
Abstract: Structure, surface properties and morphology of a regioirregular conjugated poly(3‐thiophene acetic acid) (PTAA ) and four polyelectrolytes based on PTAA with various cations were studied by using FT‐IR, 1 H‐NMR spectroscopy and SEM. The properties of PTAA and its polyelectrolytes depend on the unique combination of a hydrophobic backbone and hydrophilic ionic side groups. The thermal stability, fluorescence and conductivity properties were investigated. These polymers exhibited fluorescence emissions at about 565 nm characterized for the π‐conjugated polythiophene. Undoped polymers have a better conductivity than previous polymers.